Kontribusi antara Kualitas Pelayanan dengan Kepuasan Konsumen di Fore Coffe Kota Padang - Insani, Dea Putri; Rinaldi, Rinaldi (Lembaga Yasin AlSys, 2024)
The purpose of this research is to find out how much service quality contributes to consumer satisfaction at Fore Coffee, Padang city. This research uses quantitative methods. The sampling technique was using purposive sampling among the people of Padang city, namely Fore coffee consumers with a total of 277 research subjects. The research instrument for data collection used the service quality scale from Parasuraman, Zeithmal and Berry (1998) and the consumer satisfaction scale from Kolter (2000). Data was obtained using simple regression analysis. The results of the hypothesis test are known to be significant from the regression with an F value of 16.055 and a p value of 0.000. The p value can show <0.05, so it can be concluded that the independent variable service quality contributes to the dependent variable consumer satisfaction, so it can be seen that the hypothesis in the research is acceptable (Ha).